E-learning in fundamental disciplines teaching for engineering students; SGEM. 3rd International Multidisciplinary Scientific Conference on Social Sciences and Arts; Bk. 1, vol. 3 - Demenkova L. G. Larisa Gennadievna; Berezovskaya O. B. Olga Borisovna; Knyazeva O. G. Olga Gennadjevna; Sidorenko A. S. Alena Sergeevna (2016, 2016)
Title screen